2022
DOI: 10.4178/epih.e2022058
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of functional disability and its impact on older adults in the ASEAN region: a systematic review and meta-analysis

Abstract: Objectives: Functional disability is a common consequence of the ageing process and can lead to poor health outcomes due to the inability to perform activities of daily living (ADL) and instrumental ADL (IADL) independently. However, the prevalence of functional disability among older adults in the ASEAN region is poorly documented. This study aims to assess the prevalence of functional disability and its impact on older adults in the ASEAN region.Methods: A systematic literature search was performed on four d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 44 publications
2
11
0
Order By: Relevance
“…Compared to these prevalence rates of functional disability in Thailand (<10%), much higher rates were found among older adults (≥50 years) in the six LMICs, namely, China (16.2%), India (55.7%), Ghana (44.0%), South Africa (38.6%), Mexico (38.8%), and Russia (43.1%) (15). Furthermore, we found that consistent with previous research (6,9,15,29,32,38,40), both MM and functional disability increased with age, decreased with higher education, and decreased with higher income. In line with previous studies (32), the prevalence of MM was higher in women than in men, while functional disability did not differ by sex, as found previously (29,38,39).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Compared to these prevalence rates of functional disability in Thailand (<10%), much higher rates were found among older adults (≥50 years) in the six LMICs, namely, China (16.2%), India (55.7%), Ghana (44.0%), South Africa (38.6%), Mexico (38.8%), and Russia (43.1%) (15). Furthermore, we found that consistent with previous research (6,9,15,29,32,38,40), both MM and functional disability increased with age, decreased with higher education, and decreased with higher income. In line with previous studies (32), the prevalence of MM was higher in women than in men, while functional disability did not differ by sex, as found previously (29,38,39).…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, we found that consistent with previous research (6,9,15,29,32,38,40), both MM and functional disability increased with age, decreased with higher education, and decreased with higher income. In line with previous studies (32), the prevalence of MM was higher in women than in men, while functional disability did not differ by sex, as found previously (29,38,39). The prevalence of MM and functional disability was higher among those who were physically inactive, which is consistent with previous research (32,34,40,43,44).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Chan School of Public Health, Office of Human Research Administration (ref. C13–1608–02), and the Mpumalanga Provincial Research and Ethics Committee” 6 . All participants provided written informed consent.…”
Section: Ethics Statementmentioning
confidence: 99%
“…3 Among older adults in South Africa, 37.2% of the participants had "moderate or severe and/or very severe functional disability." 4 Functional disability is associated with increased hospitalization, 5 poor self-rated quality of life, 6 and mortality. [7][8][9] Therefore, it would be important to identify modifiable factors, such as mental symptoms, that can delay or prevent functional disability from occurring in older age.…”
Section: Introductionmentioning
confidence: 99%